The influence of Spraino© on performance and safety in badminton - Gertz Lysdal, F. (6th World Congress of Racket Sport Science, 2018)
High shoe-surface friction is in many ways viewed as fundamental to high badminton performance, but it is also associated with an increased risk of lower-extremity injuries. Lateral ankle sprains are the most-frequent injury in badminton accounting for more than 20% of all acute injuries. An innovative preventive approach is to reduce friction along the lateral edge of the shoe using Spraino®. This allows the foot to be repositioned before an injury occurs. Twenty-one international elite-level badminton players participated in a randomized crossover study, with the primary purpose of investigating whether Spraino® can be used in badminton without compromising performance and/or safety during a badminton-specific Speed Test. The secondary aims were to investigate lower extremity kinematics and foot positioning. The results revealed a strong trend (p=0.08) towards a better performance when using Spraino® with completion times of 31.0 ± 2.2s (Spraino) and 31.5 ± 2.4s (Control). No changes were found in lower extremity kinematics and no additional horizontal movement (sliding) was shown despite initial contact on the lateral aspect of the heel. The trend towards a faster completion time highlights, that Spraino® may be effective when used to prevent ankle sprains in badminton, without affecting performance and safety.